Analisis Performa Klaster Single Board Computer dalam Implementasi Singular Value Decomposition - Azka, Syahrul; Liebenlito, Muhaza; Sutanto, Taufik Edy (Universitas Negeri Gorontalo, 2025)
This study aims to evaluate the performance of Singular Value Decomposition operations based on the divide-and-conquer method on two computing cluster architectures: an Intel Core i5-12400-based PC cluster and an Allwinner H618-based Orange Pi Zero 3 Single Board Computer cluster. The evaluation focuses on three key metrics: execution time, speedup, and energy consumption. Experiments were conducted on three matrix sizes (2160×2160, 3240×3240, and 5400×5400) with processor cores ranging from 1 to 12. Energy consumption was measured using a wattmeter by recording peak power during execution. The results show that the PC cluster achieves faster execution times but exhibits limited parallel scalability, reaching a maximum speedup of 10.31× and energy consumption of 2.07 Wh for the 5400×5400 matrix with 12 cores. In contrast, the SBC cluster demonstrates significantly higher parallel efficiency, achieving a speedup of 117.75× with energy consumption of only 0.23 Wh under the same configuration. These findings indicate that the SBC cluster offers a promising energy-efficient, cost-effective solution for parallel numerical computing, particularly for sustainable computing infrastructure in higher education, in alignment with the Sustainable Development Goals 7.